Recurrent rupture of an infected femoral artery pseudoaneurysm secondary to a 35-year-old plated arthrodesis: A case report - Dan Y. Draytsel; Deena B. Chihade; Michael J. Costanza; Anthony Feghali (Annals of Vascular Surgery - Brief Reports and Innovations)
Femoral endarterectomy with patch angioplasty is the standard of care for patients suffering from chronic limb-threatening ischemia with significant inflow disease. Despite avoidance of prosthetic and increased use of biologicanalogs, graft infection remains a risk. We describe a patient with recurrent infected femoral artery pseudoaneurysm who underwent appropriate work-up that failed to implicate a source initially. This case highlights the dilemma of patch selection in the face of recurrent infection, the importance of collaborative efforts of three specialties to identify that source and the paucity of studies linking orthopedic hardware to infectious complications associated with vascular grafts.